2018
DOI: 10.1007/s00068-018-0953-4
|View full text |Cite
|
Sign up to set email alerts
|

Platelet transfusion increases risk for acute respiratory distress syndrome in non-massively transfused blunt trauma patients

Abstract: Pre-emptive platelet transfusion should be avoided in non-massively transfused blunt injury victims in the absence of true or functional thrombocytopenia, as it increases risk for ARDS with no survival benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
1
9
0
2
Order By: Relevance
“…Kasotakis and coworkers investigated the effect of platelet transfusions in multiple trauma patients. According to their results, high-volume platelet transfusions are associated with the development of ARDS [ 52 ]. This supports the theory of a detrimental effect of platelets on lung physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Kasotakis and coworkers investigated the effect of platelet transfusions in multiple trauma patients. According to their results, high-volume platelet transfusions are associated with the development of ARDS [ 52 ]. This supports the theory of a detrimental effect of platelets on lung physiology.…”
Section: Discussionmentioning
confidence: 99%
“…On the opposite, Sambasivan and colleagues reported that high ratios of platelet unit:RBC (> 1:2) administrated to non-massively transfused trauma patients had no effect on mortality compared to low ratios (≤ 1:2) but significantly decreased ventilator-free and ICU-free days [ 20 ]. In another study also including non-massively transfused blunt injury victims, platelet transfusion was found to increase the risk of acute respiratory distress syndrome without any survival benefit, but platelet transfusion was recorded over 48 h and only 488 patients were included [ 21 ]. Our study provided the opportunity to examine a large cohort of trauma patients and suggested that early platelet transfusion improved survival, not only in massively transfused patients but also in severely bleeding trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…An association has been described between prophylactic PTs in invasive procedures and an increased risk for thrombosis and mortality, between prophylactic PTs in patients with intracranial hemorrhage and a greater mortality and worsening of the neurological condition, between PTs and an increased risk for respiratory distress in patients with major trauma, and between PTs and an increased risk for mortality and complications in patients undergoing myocardial revascularization surgery. [143][144][145][146] However, other studies in adults reported that a prophylactic PT is not associated with a greater risk. [147][148][149] A recent systematic review failed to draw conclusive conclusions in this regard.…”
Section: Megaplatelet Inclusion Bodymentioning
confidence: 99%